Climatic stresses and rural emigration in Guatemala - Britos, Braulio; Hernandez, Manuel A.; Puricelli, Estefania; Sahajpal, Ritvik (International Food Policy Research Institute, 2023)
International migration is a recurrent and growing phenomenon and a large share of emigrants originate from rural areas. This study examines the association between climatic stresses and rural emigration in Guatemala. We exploit variations on climatic stress situations and emigration flows at the subnational level and over time to examine whether the observed migration dynamics can be explained by the occurrence of specific adverse weather events. We find that drought periods affect emigration positively the following year, especially among men, while periods of high temperatures and low soil moisture affect male and female emigration negatively. The results are generally not much sensitive to alternative model specifications and estimations. The apparent mixed findings point to both direct effects where climatic stresses may encourage people to migrate in search of better opportunities, as well as indirect effects in the sense that climatic stresses affect agricultural productivity and household liquidity, which may prevent people from migrating despite their willingness to emigrate.